Secure image transcoding technique using chaotic key based algorithm with improved security - Anoop, B. N.; George, S. N.; Deepthi, P. P. (2013 International Multi-Conference on Automation, Computing, Communication, Control and Compressed Sensing (iMac4s), 2013)
Transcoding is the direct digital-to-digital data conversion of one encoding to another. This paper proposes a system of secure image transcoder which mainly focuses on multimedia applications such as web browsing through mobile phones, in order to improve their delivery to client devices with wide range of communication, storage and display capabilities. In this work, we propose a secure image transcoding technique based on a chaotic key. To improve the security of the above mentioned system, we have incorporated a variable block size selection prior to this stage. We analyzed the security of the proposed system and it is proved that the proposed system is highly secure against several forms of attack. The performance of the system is evaluated for different images and it is verified that the system is having less resource complexity with good performance.